Two Arabidopsis Homologs of Human Lysine-Specific Demethylase Function in Epigenetic Regulation of Plant Defense Responses - Noh, Seong Woo; Seo, Ri-Ra; Park, Hee Jin; Jung, Ho Won (Frontiers in Plant Science, 2021)
Epigenetic marks such as covalent histone modification and DNA methylation are crucial for mitotically and meiotically inherited cellular memory-based plant immunity. However, the roles of individual players in the epigenetic regulation of plant immunity are not fully understood. Here we reveal the functions of two Arabidopsis thaliana homologs of human lysine-specific demethylase1-like1, LDL1 and LDL2, in the maintenance of methyl groups at lysine 4 of histone H3 and in plant immunity to Pseudomonas syringae infection. The growth of virulent P. syringae strains was reduced in ldl1 and ldl2 single mutants compared to wild-type plants. Local and systemic disease resistance responses, which coincided with the rapid, robust transcription of defense-related genes, were more stably expressed in ldl1 ldl2 double mutants than in the single mutants. At the nucleosome level, mono-methylated histone H3K4 accumulated in ldl1 ldl2 plants genome-wide and in the mainly promoter regions of the defense-related genes examined in this study. Furthermore, in silico comparative analysis of RNA-sequencing and chromatin immunoprecipitation data suggested that several WRKY transcription factors, e.g., WRKY22/40/70, might be partly responsible for the enhanced immunity of ldl1 ldl2. These findings suggest that LDL1 and LDL2 control the transcriptional sensitivity of a group of defense-related genes to establish a primed defense response in Arabidopsis.